Changes in the Perception of the Sumbawa Community in the Nyorong Tradition Sumbawa Regency - *Sukarddin Sukarddin; Lili Suryaningsih (Riwayat: Educational Journal of History and Humanities, 2022)
The purpose of this study was to determine changes in people's perceptions of the nyorong tradition. This study describes the Sumbawa people's perception of the Nyorong tradition found in the Nyorong culture in Sumbawa district. This research is a type of qualitative research. The method used is descriptive analysis. The source of the data in this study is the perception of the Sumbawa people obtained from the informants. The data in this study were in the form of recordings which were analyzed based on community responses. Based on the results of the discussion, there is the elimination of traditions at several stages in the Nyorong incident due to financial and external cultural influences resulting in the Sumbawa people leaving their pure identity in the form of practicing marriage with a series of applications, determining the day, Kabul consent then finally thanksgiving. The loss of the nyorong tradition during the delivery of the dowry, which previously occurred in the nyorong event, preparing equipment for the nyorong event, packing luggage, forming a nyorong committee, preparing the nyorong arena, carrying out the nyorong attraction), old replay (reply to rhymes).